Persepsi Siswa terhadap Pembelajaran Daring (Studi Kasus pada Siswa Kelas X SMA Negeri 2 Bondowoso) - Sari, Serly Puspita; Widodo, Joko; Tiara, Tiara (Universitas Pendidikan Ganesha, 2023)
This study aims to determine student perceptions of online learning in class X SMA Negeri 2 Bondowoso. This research is a descriptive quantitative research with data collection methods used, namely questionnaires, interviews, and documents. The subjects in this study were class X students of SMA Negeri 2 Bondowoso. The results of the research show that students' perceptions of online learning vary in terms of learning processes indicators and support. Students are less interested in learning online because they cannot interact smoothly with the teacher. In addition, students find it difficult to understand the material and do assignments because the assignments given are disproportionate. However, students can work on assignments independently. On the support indicator, some students receive support from related parties, including schools, government, and student guardians.